Effect of Young Coconut Water Concentration on Bud Chip Germination Phase on Several Parts of Sugar Cane (Saccharum officinarum L.) Stems - Puspitasari, Alfarizi Arinta Rury; Machmudi; Septia, Erfan Dani; Alfarizi, Rifqi Ahmad (Universitas Muhammadiyah Malang, 2023)
The germination phase is a crucial stage in the successful cultivation of sugarcane. Seeds obtained from six to eight-month-old gardens, extracted from sugarcane stems' protrusions, are used. These seeds have dormant bud characteristics, making them suitable for germination. Typically, a single sugarcane stem contains at least 13 buds, and farmers usually select seeds with 2-8 eyes per spike. However, excessive use of buds may result in abnormal seed growth, emphasizing the need for careful selection. The study utilizes the rase cage test system, dividing the sugarcane stem into upper, middle, and bottom sections to determine the optimal bud quantity in each treatment. It investigates the response of different parts of sugarcane bud chip stems to varying concentrations of coconut water growth regulator during germination. Employing a factorial randomized block design, the study includes two factors: Bud chip (BA: Upper Stem, BT: Middle Stem, BB: Bottom Stem) and coconut water growth regulator concentration (Z1: 25%, Z2: 50%, Z3: 75%, Z4: 100%). The positive control involves Agrogibb at a concentration of 120 ppm, with all treatments soaked for six hours. Conducted at the Indonesian Sugar Plantation Research Center on January 10, 2023, the study reveals that the BBZ1 treatment significantly affects the observed parameter of shoot emergence, with an average of 8.1 days. Conversely, the BAZ1 treatment shows the fastest and most efficient shoot emergence, with an average of 5.1 days, outperforming other treatments. These findings emphasize the significance of careful selection and treatment during the germination phase for optimal sugarcane productivity.